(untitled) (Research, Society and Development, 2021)
Public Research Institutions (PRI) have missions defined by law for society. The article aims to analyze the spatiality of PRI patent production. Therefore, the development territories of the state of Piauí and their economic vocations were related based on literature and government agencies. For patents, the documents of technologies developed by those in Piauí were searched and their titles and abstracts were analyzed. 98 patents were found, 39 of which relate to the economic vocations of Piauí and their resources. A total of 160 interactions were identified, with emphasis on agroindustry and beekeeping. The territories Entre Rios and Cocais have the highest number of relationships, however, when the relationships in the semiarid region are added, the highest concentration is observed (85). Thus, the interactions between development territories and technological production are considered crucial for improving people’s lives, although it is necessary to promote the arrival of these technologies for social and productive arrangements through Technology Transfer.